Commissural Gain Control Enhances the Midbrain Representation of Sound Location - Orton, Llwyd David (J Neurosci, 2016)
Accurate localization of sound sources is essential for survival behavior in many species. The inferior colliculi (ICs) are the first point in the auditory pathway where cues used to locate sounds, ie, interaural time differences (ITDs), interaural level differences (ILDs), and pinna spectral cues, are all represented in the same location. These cues are first extracted separately on each side of the midline in brainstem nuclei that project to the ICs. Because of this segregation, each IC predominantly represents stimuli in the contralateral hemifield. We tested the hypothesis that commissural connections between the ICs mediate gain control that enhances sound localization acuity. We recorded IC neurons sensitive to either ITDs or ILDs in anesthetized guinea pig, before, during, and following recovery from deactivation of the contralateral IC by cryoloop cooling or microdialysis of procaine. During deactivation, responses were rescaled by divisive gain change and additive shifts, which reduced the dynamic range of ITD and ILD response functions and the ability of neurons to signal changes in sound location. These data suggest that each IC exerts multiplicative gain control and subtractive shifts over the other IC that enhances the neural representation of sound location. Furthermore, this gain control operates in a similar manner on both ITD- and ILD-sensitive neurons, suggesting a shared mechanism operates across localization cues. Our findings reveal a novel dependence of sound localization on commissural processing. SIGNIFICANCE STATEMENT Sound localization, a fundamental process in hearing, is dependent on bilateral computations in the brainstem. How this information is transmitted from the brainstem to the auditory cortex, through several stages of processing, without loss of signal fidelity, is not clear. We show that the ability of neurons in the auditory midbrain to encode azimuthal sound location is dependent on gain control mediated by the commissure of the inferior colliculi. This finding demonstrates that commissural processing between homologous auditory nuclei, on either side of the midline, enhances the precision of sound localization.